Developing Students Emotional Learning through English Instructions Visual E-Book - Ishak; Mulyanah, Euis Yanah (International Journal Linguistics of Sumatra and Malay, 2023)
The purpose of this study was to investigate whether the visual English instructions was effectively used in developing students emotional in learning English. The research method used quantitative approach. The design of this study was a quasi-experimental study to determine the effectiveness of using visual book English instructions on students' emotional learning especially in English. The population of this research are the students of primary school in Tangerang District. The sample of this research is 80 respondents. The results showed that there was a significant difference between students' emotional learning through visual e book English Instructions the pre-test and post-test. After being given treatment, their understanding in the instruction they use in the classroom in the teaching learning process increased significantly by up to 18 percent. This can be seen from the average pre-test result in the experimental class of 76.50, and the post-test average of 82.28. The average pre-test result in the control class was 69.84, and the average post-test result was 66. The t-test value was greater than the t-table (9.34 > 2.00). This shows that the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. It can be concluded that the use of visual e book English instruction is effective in developing students' emotional in learning English.